Primary invasive squamous cell carcinoma of the nipple in an adult male: A case report and brief review of literature - Priyansh Jain; Prapti Acharya; Mahesh Sultania; Dillip K. Muduly; Mukund N. Sable (Indian Journal of Pathology and Microbiology, 2023)
This is a case report of a rare and uncommon primary invasive squamous cell carcinoma (SCC) of the nipple in a male patient. The patient presented with an ulcerated growth over the left nipple for the last 20 years, which progressed over the last 6 months. He underwent wide local excision with level II axillary lymph node dissection, and one out of 42 lymph nodes harvested showed metastatic deposit. The patient was planned for follow-up with no adjuvant treatment, and had no evidence of local-regional or distant recurrence at 24 months follow-up. The primary invasive SCC of male nipple is very rare, and its diagnosis is challenging as it can be confused with other clinical conditions. However, a histopathological examination with immunohistochemistry can differentiate primary SCC nipple from other differential diagnoses. The treatment options for cutaneous SCC include surgical excision, cryotherapy, electrosurgery, topical ointments, definitive radiation therapy, and photodynamic therapy. Regional lymph node dissection in SCC nipple could potentially have therapeutic and prognostic significance.